Efektivitas Penerapan Model Quantum Learning Untuk Meningkatkan Karakter Patriotisme Pada Mata Pelajaran PKn Sekolah Dasar - Nurul Hidayati Zahro; Arief Cahyo Utomo (Elementary Teacher Education Program, Majalengka University, 2024)
This study was motivated by the weak patriotism character of students due to the use of inappropriate learning models that make students feel bored and uninterested in Civics lessons. This study aims to determine the application and effectiveness of the Quantum Learning model to improve the character of patriotism in Civics subjects for grade V students at SDN 2 Bacem. The research method used by researchers is a quasi-experimental method with exsperimental designs. Data collection techniques using observation, questionnaires, and documentation. Data analysis used homogeneity test, normality test, and T-test. The results of this study indicate that learning with the application of the Quantum Learning model is effective and can improve the character of patriotism in Civics subjects for grade V students at SDN 2 Bacem. This is evident in the results of the T-test, it is known that the significance value is 0.033 <0.05 and the value of t_count>t_table is 2.408>1.782, meaning that H_0 is rejected and H_1 is accepted. It is also proven by the comparison of the average value of the initial questionnaire and the final questionnaire has increased by 2.77.Keywords: Effectiveness; Quantum Learning; Patriotism Character